DINAMIKA INTEGRASI DAN PEMISAH POLRI DARI ABRI TAHUN 1961-2002 - Aini, Aulia Nur Wihdlatil; Muntholib, Abdul; Suryadi, Andy (Jurusan Sejarah Fakultas Ilmu Sosial Universitas Negeri Semarang, 2019)
The purpose of this research are: (1) to reveal how the process of Indonesian National Police integration into ABRI in 1961-1998, (2) to reveal how the separated process of Indonesian National Police from ABRI in 1998-2002. This research uses historical research methods that contain four steps, those are: heuristics, source criticism, interpretation and historiography. The results of this research show that the Indonesian National Police have an important role in the revolutionary period along with other armed forces, so that become a main reason Indonesian National Police join into ABRI . The integration of Indonesian National Police into ABRI has caused many pros and cons. The impact of the integration made the performance of the Indonesian National Police very deteriorating in the operational and guidance section. With the existence of various obstacles after the integration of Indonesian National Police into the Armed Forces finally in 1999 the National Police separated from ABRI. Keywords: Integration, Separation, Polri, ABRI